Does Transformational Leadership Impact Organizational Resilience? The Mediating And Moderating Role of Organizational Innovation - Alden Nelson; Yolanda Masnita; Husna Leila Yusran; Agustinus Setyawan (International Journal of Business and Quality Research, 2025)
The leadership role is essential to promote resilience when handling the crises and organization shall focus for recovery to maintain competitive advantage. The study investigates transformational leadership to organizational innovation and organizational resilience and how organizational innovation act as a mediator between transformational leadership to organizational resilience. Quantitative research was used in this study and SEM PLS 4.0 was used to process data from 125 respondents in MNC manufacturing. The result shown that transformational leadership unable to influence organizational resilience but organizational innovation has effect to influence organizational resilience. When organizational innovation applied as mediating role, it can affect the transformational leadership to organizational resilience. This study only focus on how the transformational leadership and organizational innovation affect organizational resilience, in MNC manufacturing. The future study advised to broaden the scope to other places in Riau Islands or Indonesia more generally. Other variables such as adaptive capacity and self-efficacy can be used to further test the factors that influence Organizational Resilience in an organization. This study contributes theoretically to advancing knowledge on how organizational resilience and leadership styles correlate in multinational companies. In practice, this study can provide guidance for professionals in encouraging innovation and transformational leadership to enhance the resilience of multinational companies.